Gestión de morosidad y su relación con la rentabilidad en Caja Municipal de Ahorro y Crédito Piura SAC Iquitos periodo 2021 - Caparachin Alva, Andrea Estefany (2024)
The objective of this research was to identify the relationship between delinquency management and profitability in the Caja Municipal de Ahorro y Crédito Piura SAC, Iquitos, period 2021; With a type of quantitative research, of a non-experimental design and a type of cross-sectional design with a correlational scope, it included as a population 02 financial statements (statement of financial situation and the statement of results) in addition to a survey carried out with 33 workers, including managers and operatives; The results found were the degree of correlation between the default management variable and profitability determined by Spearman's Rho with a value of 0.438 for both variables; An ROE of 2.33% was determined, which indicates that the company generates a return of 2.33% on equity, suggesting that the company is generating a modest profitability, an ROA of 0.57%, which indicates that the company generates a return of 0.57%. on its total assets; The work concluded that there is a medium positive correlation between delinquency management and profitability; suggesting that effective management of delinquency can positively influence the profitability of the entity, in addition that Caja Piura has appropriate policies and practices to manage delinquency and credit risk, with respect to profitability indicators suggesting that the Caja Piura did not achieve high profitability during 2021, especially in terms of return on assets and operational efficiency.